The perception of form and colour and its relation to impulsivity in children with specific reference to the attention deficit hyperactivity disorder - Vitali, Lucia (Stellenbosch : Stellenbosch University, 2012)
Thesis (M.A.) -- University of Stellenbosch, 1995.